The Incidence and Risk Factors for the Presence of Type 1B or Type 3 Utero-ovarian Anastomoses During Uterine Artery Embolization - Bora Peynircioğlu; Barbaros Erhan Çil; Fatma Gonca Eldem; Ferdi Çay (Genel Tıp Dergisi)
Background/Aims: Demonstration of possible utero-ovarian anastomoses (UOA) before or during uterine artery embolization (UAE) is important to preserve ovarian reserve. This study aimed to evaluate the incidence and risk factors for the presence of type 1b or type 3 UOA in patients undergoing UAE for the treatment of uterine myomas. Methods: Procedural angiographies of patients who underwent UAE were evaluated in a single academic center. Patients’ demographics, indication for UAE, presence and type of UOA, presence of adnexal pathology at preprocedural MRI, history of pelvic surgery, and total uterine volume at preprocedural MRI were retrospectively evaluated. Analysis of the aforementioned variables between patients with and without UOA was performed. Results: This study included 30 patients with a mean age of 41.97±5.72 years (range 32 - 56). UOA was found in 17 (56.6%) patients, 10 (33.3%) of them were type 1b, and 7 (23.3%) of them were type 3. Five patients (17.2%) had adnexal pathology at pre-procedural MRI and 12 patients (40%) had a history of pelvic surgery. The mean total uterine volume was 607.1 cm3. In the analysis of variables between patients with and without UOA, UOA presence was significantly higher in patients with a history of pelvic surgery (p=0.005). All of the patients with a history of myomectomy were found to have type 1b or type 3 UOA. No significant relation between UOA and age, the presence of adnexal pathology, and uterine volume were detected. Conclusion: Utero-ovarian anastomoses are commonly encountered during UAE. A history of pelvic surgery was found to be a risk factor for the presence of type 1b and type 3 UOA.